How do incentives affect creativity? - Katharina Eckartz; Oliver Kirchkamp; Daniel Schunk (Center for Economic Studies and ifo Institute (CESifo), 2012)
We compare performance in a word based creativity task under three incentive schemes: a flat fee, a linear payment and a tournament. Furthermore, we also compare performance under two control tasks (Raven's advanced progressive matrices or a number-adding task) with the same treatments. In all tasks we find that incentives seem to have very small effects and that differences in performance are predominantly related to individual skills.
Keywords: C91; J33; 330; creativity; incentives; real effort task; experimental economics; Kreativität; Ökonomischer Anreiz; Arbeitsleistung; Qualifikation; Test